Ответ:)
Пошаговое объяснение:
1) а) 31 + 2х = 55 + 3х
2х - 3х = 55 - 31
- х = 24
или же х = -24, как пойдёт
б) -15 - 4х = -8х + 45
-4х + 8х = 45 + 15
4х = 60
х = 15
в) 5y + 15 = 4y + 20
5y - 4y = 20 - 15
y = 5
2) a) -3(3b + 1) - 12 = 12
-9b - 3 - 12 = 12
-9b = 3 + 12 + 12
-9b = 27
b = -![\frac{27}{9} \frac{27}{9}](https://tex.z-dn.net/?f=%5Cfrac%7B27%7D%7B9%7D)
b = -3
б) (2 - c) + 3(c - 3) = -13
2 - c + 3c - 9 = -13
-c + 3c = -13 - 2 +9
2c = -6
c = -![\frac{6}{2} \frac{6}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B6%7D%7B2%7D)
c = -3
в) 3,4 + 2y = 7(y - 2,3)
3,4 + 2y = 7y - 16,1
2y - 7y = -16,1 - 3,4
-5y = -19,5
y = ![\frac{19,5}{5} \frac{19,5}{5}](https://tex.z-dn.net/?f=%5Cfrac%7B19%2C5%7D%7B5%7D)
y = 3,9